Effectiveness of 5-Fluorouracil Chemotherapy in Preventing Recurrence of Ocular Surface Squamous Neoplasia - Khan, Sumeya Ali; Ullah, Saad; Manzoor, Amna; Taimur, Fariha; Tahir, Faizan; Sameen, Murtaza (Journal of Rawalpindi Medical College, 2025)
Objective Ocular surface squamous neoplasia (OSSN) encompasses a spectrum of malignancies affecting the conjunctival and corneal tissues, including conjunctival intraepithelial neoplasia (CIN) and squamous cell carcinoma (SCC). High recurrence rates for OSSN necessitate effective treatment strategies, particularly in low-resource settings. Methodology This prospective case series, conducted from March 2023 to March 2024 at the Department of Orbit and Oculoplastics, Alshifa Trust Eye Hospital, Rawalpindi, included 34 eyes from 34 patients with biopsy-confirmed OSSN. Patients underwent surgical excision with a 4 mm clear margin, followed by applying 1% 5-fluorouracil (5-FU) for 90 seconds and cryotherapy using a double freeze-thaw cycle. Post-surgical patients received topical 5-FU in cycles: one week on and three weeks off, for three to five months. Outcomes were documented through clinical examination and anterior segment optical coherence tomography (OCT). Primary outcomes were recurrence of clinical lesions. The secondary outcome was detecting the presence of HIV in patients by using an HIV antibody titres assay. Results The mean age of patients was 53.3 years. 73.5% were males, and 26.5% were females. The majority (76.5%) were diagnosed with full-thickness dysplasia. Treatment was predominantly post-excision. Chemoreduction prior to surgery was done in 4 patients. Most had 3 cycles of 5-FU (52.9%). During follow-up, not a single recurrent lesion occurred. Logistic regression indicated a positive, though non-significant, association between the number of 5-FU cycles and reduced recurrence (β = 0.2598, p = 0.321). Conclusion This study demonstrates that using 5-FU with cryotherapy significantly reduces OSSN recurrence in low-resource settings. Further research with larger cohorts is recommended to confirm these findings and refine treatment protocols. Keywords 5-Fluorouracil, Cryotherapy, chemotherapy protocols, Squamous Cell neoplasm, Conjunctival disease